Reservoir Fluid Monitoring Using 4D Seismic and Rock Physics Models in a Producing Field in Malay Basin - DANAEI, SHAHRAM (2017)
Time-lapse seismic technique is gaining popularity among oil and gas companies to depict the dynamic changes inside oil and gas reservoirs. Reservoir dynamic changes (saturation and pore pressure) due to production and/or injection activities appear in time-lapse seismic surveys as 4D signal. It is prudent to run a 4D feasibility modelling before launching a time-lapse seismic project. In this research, 4D feasibility modelling was conducted for an oil reservoir in Malay basin using a developed rock physics model. For water saturation modelling, Gassmann fluid substitution was used and for pore pressure modeling, Hertz-Mindlin geo-mechanical approach in conjunction with pore space stiffness theory had been utilized. The capability of AVO intercept and gradient attributes also been investigated to quantify between the pressure and saturation changes. The result of rock physics model demonstrates changes in elastic properties due to various reservoir pressures and water saturations. The outcome of the AVO intercept and gradient cross-plot also proves the capability of this method to distinguish between pore-pressure and saturation changes. In the cross-plot domain, pore pressure changes are aligned in a different direction compared to water saturation alterations make it possible to separate these two dynamic changes. The 4D feasibility and AVO modelling were followed by a time-lapse seismic qualitative interpretation for Angsi field in Malay basin. The field has been under production and water injection for nearly six years; therefore, a precise time-lapse seismic qualitative interpretation provides us with tools to monitor the movement of injected water in the target reservoir. Six various seismic attributes including 4D inversion were used to analyze 4D seismic data set. All 4D seismic attributes show the similar result which indicates the high accuracy in 4D qualitative interpretation. From 4D qualitative interpretation, the distribution of injected water after six years is evident in all 4D seismic attributes. Analyzing 4D signals answers the reason for water breakthrough in a producer well and reveals the location of unswept oil in the field.